The outcome and the influencing factors of the age of onset in post-mortem of chronic bronchitis patients: a retrospective study - Zhu L; Ni Z; Luo X; Zhang Z; Wang S; Meng Z; Gu X; Wang X (International Journal of COPD, 2018)
Linyun Zhu,1 Zhenhua Ni,2 Xuming Luo,1 Zhuhua Zhang,1 Shiqiang Wang,1 Ziyu Meng,1 Xiandong Gu,1 Xiongbiao Wang1 1Department of Respiratory Medicine, Putuo Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, 2Central Laboratory, Putuo Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, China Purpose: Chronic bronchitis is thought to occur in elderly patients, and smoking seems to be an important risk factor. The outcomes related to the age of onset in patients with chronic bronchitis are still unclear. Patients and methods: A retrospective study was conducted on deceased patients whose diagnosis included bronchitis from 2010 to 2016. Patients were separated into two groups according to the age of onset (Group I, age ≤50 years old; Group II, age >50 years old). Information regarding disease course, smoking history, death age, number of admissions per year, Hugh Jones Index, and self-reported comorbidities of the patients was recorded. Results: The courses of chronic cough and sputum were 33.38±7.73 years and 14.44±8.60 years in Group I and Group II, respectively (p<0.05). The death ages of Group I and Group II were 77.65±7.87 years and 84.69±6.67 years, respectively (p<0.05). There was a significant negative correlation between the number of hospital admissions per year and the age of onset. The age of onset was negatively associated with daily smoking count (r=-0.210) and total smoking count (r=-0.146). In Group I, there were fewer cases of coronary heart disease (OR =0.41 [0.24–0.71]), neurological diseases (OR =0.48 [0.24–0.97]), and total comorbidities (OR =0.67 [0.54–0.85]) than in Group II. Conclusion: Patients with early onset chronic bronchitis had a longer history, younger death age, poorer health status, and lower incidence of comorbidities. Keywords: chronic airway disease, comorbidity, Hugh Jones Index, smoking, hospital admission, disease course